A52: The Impact of Adalimumab on Growth in Patients With Juvenile Idiopathic Arthritis. Issue 11 (March 2014) - Lovell, Daniel J.; Ruperto, Nicola; Jarosova, Katerina; Nemcova, Dana; Vargova, Veronika; Michels, Hartmut; Chalom, Elizabeth; Ilowite, Norman; Wouters, Carine; Brunner, Hermine; Kupper, Hartmut; Giannini, Edward; et al.
Abstract : Background/Purpose: Children with juvenile idiopathic arthritis (JIA) often exhibit growth impairments. Treatment with adalimumab (ADA) has been shown to be safe and effective in JIA patients (pts) when dosed every other week (eow) for up to 3 years, but the effect of ADA on growth is not known. The purpose of this post hoc analysis is to describe growth parameters in pts with JIA treated with ADA in a clinical trial setting. Methods: Pts aged 4–17 with polyarticular course JIA were enrolled in a phase 3, randomized‐withdrawal, double‐blind (DB), stratified, parallel‐group study, which consisted of a 16‐wk open‐label (OL) lead‐in phase, a 32‐wk DB phase, and an OL extension (OLE) phase. In the OLE phase, pts were dosed based on body surface area (24 mg/m 2, max 40 mg dose), followed by a switch to 20 or 40 mg eow based on a body weight of ≤30 kg or >30 kg, respectively. To enter the DB phase, pts had to achieve an American College of Rheumatology Pediatric score ≥30% (ACR Pedi 30) during the OL lead‐in. Pts could enter the OLE after 32 wks in the DB phase or at time of first flare (whichever came sooner). For this analysis, all pts who received ≥1 dose of ADA ± methotrexate (MTX) were included and pts were grouped by baseline height into 4 categories: <5 th, ≥5 th –<25 th, ≥25 th –<50 th, and ≥50 th percentile based on the US Centers for Disease Control and Prevention (CDC) growth charts. Mean CDC percentile changes in height, weight, and body mass index (BMI) percentiles were calculated through 250 weeks. Growth and efficacy data were analyzed as observed. Results: Among the 171 pts enrolled in this study, 79% were female with a mean age of 11.1 years. 28 (16%) were in the <5 th percentile, and these pts had a significantly different baseline height (130.5 cm) and weight (33.0 kg) compared with those pts who were >5 th percentile (147.0 cm and 43.9 kg, respectively). Additionally, pts in the <5 th percentile had a significantly increased disease duration of 5.7 years compared to 3.4 years for >5 th percentile. In the <5 th and ≥5 th –<25 th percentile, pts had a larger change in mean height percentile through 250 weeks of ADA treatment (10.5, 13.5, 5.4, 4.0% change for <5 th, ≥5 th –<25 th, ≥25 th – <50 th, and ≥50 th percentile, respectively). Similar patterns were observed for BMI percentiles in these groups. ACR Pedi70 response rates improved over time in all groups, reaching 80% for <5 th, 94% for ≥5 th –<25 th, 88% for ≥25 th –<50 th, and 96% for ≥50 th percentile with ADA treatment. From baseline to the final visit, there was a decrease in the number of pts that remained in the <5 th percentile category (1 ). Conclusion: Long‐term adalimumab treatment was associated with improvement and maintenance of growth in children with JIA who were among the lowest CDC height percentiles at baseline. ADA treatment improved JIA signs and symptoms, regardless of baseline growth status.